Teaching strategies to promote autonomous learning in university students by means of Learning Management Systems (LMS) (Revista Electrónica Calidad en la Educación Superior, 2019)
Autonomous learning in university students using LMS platforms implies theoretical knowledge of the concept, as well as the implementation of various strategies that promote autonomous learning in these environments. Thus is how in a study conducted with subject teachers from the School of Social Sciences and Humanities and students currently studying hybrid distance subjects, that is, they use resources and perform some activities in LMS, it was raised as a problem of how and teachers promote strategies that promote autonomous learning in students of a distance education model that use Learning Management System (LMS)?The results obtained are related to the teachers knowledge about the concept of autonomous learning, which is consistent with the theoretical postulates in this regard. Likewise, the characteristics that identify a student who learns with autonomy and the strategies used by teachers to promote autonomous learning through LMS platforms, which contribute to both positive and negative results, and various manifestations in students are detailed on the application thereof. The conclusions discuss the importance of collaborative work for autonomous learning, the lack of methodological knowledge and the application of course strategies through LMS platforms and the need for training processes to minimize existing bias
Keywords: Distance education; LMS; learning autonomy; learning to learn; meaningful learning